Service Quality on Customer Satisfaction in Nepalese Commercial Banks - Lamichhane, Pitambar (Management Dynamics, 2018)
This paper analyzes bank customers' perception in relation to the service quality factors explaining customer satisfaction. This study has applied descriptive and regression research design using SERVQUAL approach to analyze service quality factors affecting customer satisfaction. A survey was conducted to collect data from bank customers using structural questionnaire in Kathmandu valley in 2017. All together 250 questionnaires were distributed to the bank customers and only 175 were received in usable form which represents response rate of 70 percent. Result of the study indicates that bank service quality factors affect customer satisfaction. Finally, this paper concludes that bank service quality factors reliability, assurance, tangible, empathy and responsiveness determine the level of customer satisfaction. Tangible, assurance and empathy are strong and have more explaining power of customer satisfaction in Nepalese commercial banks.